Changes in Chemical Composition and Fatty Acid Profile of Milk and Cheese and Sensory Profile of Milk via Supplementation of Goats’ Diet with Marine Algae - Ferenc Pajor; Dávid Várkonyi; István Dalmadi; Klára Pásztorné-Huszár; István Egerszegi; Károly Penksza; Péter Póti; Ákos Bodnár (Animals, 2023)
The aim of the present study was to assess the effects of the low level of Schizochytrium limacinum marine algae (daily 5 g per animal) on the milk, cheese, and whey composition; fatty acid profile of milk and cheese; and the sensory profile of goat milk using an e-nose device. Thirty Alpine goats were randomly divided into two groups: the control group (C, n = 15)—fed grass with daily 600 g concentrate and the experimental group (MA, n = 15) who received the same forage and concentrate supplemented with 5 g/head/day marine algae. Animals were kept indoors and the investigation period lasted 52 days, including the first six weeks as the period of adaptation and the last 10 days as the treatment period. During the adaptation period, bulk milk samples from each group were collected once a week (0, 7, 14, 21, 28, 35, and 42 d), while during the treatment period (10 days), bulk milk samples from each group were taken every day, and cheese samples were processed from bulk milk each day from both groups. Marine algae supplementation had no negative effect on milk composition. In contrast, the marine algae inclusion significantly elevated the fat and protein content of whey and the protein content of cheese, as well as the recovery of fat and protein in the curd, while increasing the cheeses’ moisture content on a fat-free basis. The marine algae supplementation significantly increased the docosahexaenoic acid (DHA) and the rumenic acid (CLA c9t11) concentrations and decreased the n-6/n-3 ratio in the milk and cheese. There were no significant differences between the C and the MA group with regard to the sensory profiles of the milk. It can be concluded that the milk obtained from goats given daily supplementation of 5g of MA has a fatty acid profile more beneficial to human health, without any negative effects on the milk’s aromatic components.